Repurchase Intention of Total Detergent: Halal Label and Brand Image - Nur Hidayatul Istiqomah; Ahmad Miftahur Rohim (goodwood publishing, 2022)
Purpose: The aim of the study was to investigate whether the halal label and overall reputation of the Total detergent brand influenced consumers' intentions to buy the product again. explain longer. Research methodology: To do this, the researchers used multiple linear regression analysis on a sample of 120 users in the Lowokwaru district of Malang City. The sample was selected using a questionnaire. Results: The results of the study showed that both the overall image of the brand and the perception of the halal label had an impact on the consumers' intention to purchase the product again in the future. Limitations: This research location is only in Lowokwaru district or Malang City and uses three variables Contribution: The finding would help the Detergent company to analyze customers’ repurchase intention. Suggestion: For future researchers, it is hoped that they can use or add other variables so that further research can develop more and add broader insights so that they will get better research results.